Application progress of bioactive compounds in microalgae on pharmaceutical and cosmetics. (March 2022) - Zhuang, Dingling; He, Ning; Khoo, Kuan Shiong; Ng, Eng-Poh; Chew, Kit Wayne; Ling, Tau Chuan
Abstract: Microalgae is an autotrophic organism with fast growth, short reproduction cycle, and strong environmental adaptability. In recent years, microalgae and the bioactive ingredients extracted from microalgae are regarded as potential substitutes for raw materials in the pharmaceutical and the cosmetics industry. In this review, the characteristics and efficacy of the high-value components of microalgae are discussed in detail, along with the sources and extraction technologies of algae used to obtain high-value ingredients are reviewed. Moreover, the latest trends in biotherapy based on high-value algae extracts as materials are discussed. The excellent antioxidant properties of microalgae derivatives are regarded as an attractive replacement for safe and environmentally friendly cosmetics formulation and production. Through further studies, the mechanism of microalgae bioactive compounds can be understood better and reasonable clinical trials conducted can safely conclude the compliance of microalgae-derived drugs or cosmetics to be necessary standards to be marketed. Graphical abstract: Image 1 Highlights: Integrate and analyze high-value microalgae bioactive components and their functions. Sources and extraction methods of specific microalgae bioactive ingredients are summarized. Many potential applications of microalgae-derived bioactive compounds in cosmetics/pharmaceutical products. Existing dilemmas and future industrialization trends of high bioactive ingredients from microalgae.